A Systematic Analysis of Online Marketing Materials Used by Providers of Expanded Carrier Screening. Issue 2 (February 2019) - Chokoshvili, Davit; Borry, Pascal; Vears, Danya F.
Abstract : (Abstracted from Genet Med 2018;20:976–984) Carrier screening aims to identify prospective parents at risk of having a child with a monogenic disorder. Carrier screening is primarily performed for recessive genetic disorders, for which carriers are said to be individuals who have (or carry) 1 mutated copy of the gene associated with a recessive disorder and 1 normal copy.